Drama in the classroom to improve the spoken communication skill for junior high school students - Calle E., Diana
Being a teacher is not an easy task. We have to look for new and different methods, different tools, different strategies or techniques, so students can have an active participation in developing skills in the English learning process. This work suggests teachers the use of an alternative technique called Drama. This is a powerful tool because this technique is effective and efficient when we teach English as a foreign language. Drama offers a lot of activities that teachers could use in the classroom if added to their curriculum; this activity would maintain the students? interest and keep them very motivated; thus, it will provide an excellent environment where the learning process will be fun and entertaining. In this way students will take part in these activities, increasing their creative input. The following work is focused on how this technique will help students to improve English communication. Moreover, it is going to explain how useful this method in the EFL class is. Drama was applied to a group of 40 students. It is important to mention that the students? language and their major was not English, but according to the results I got, I can assure that Drama can help students to improve speaking skills, making the EFL learning in the classroom effective.